Impact of music on the quality of life of cochlear implant users: a focus group study. (4th July 2017) - Dritsakis, Giorgos; van Besouw, Rachel M.; O' Meara, Aoife
Abstract : Objective: To study the aspects of the quality of life (QoL) on which music has an impact in adult cochlear implant (CI) users. Methods: Thirty adult CI users aged between 18 and 81 years old with a wide range of patient characteristics and musical backgrounds participated in the study. Six focus group discussions about music in everyday life were conducted and data were analysed using template analysis based on the QoL model of the World Health Organisation Quality of Life BREF questionnaire. Results and discussion: A theoretical framework of the impact of music on the QoL was developed. Music was reported to contribute to many aspects of physical, psychological, and social well-being in adult CI users. These positive effects of music on QoL were similar to what has been reported in the literature for normal-hearing adults. However, difficulties in music perception and enjoyment were found to have a negative impact on CI users' QoL, especially by causing unpleasant feelings and limited participation in music-related or routine daily activities. Conclusions: These findings suggest that an improvement in music experiences of CI users may lead to improvements in QoL and therefore support the need for music rehabilitation. However, the relative importance of music overall and of specific aspects of music for each individual should be measured for an accurate assessment of the impact of music on the QoL of CI users.